ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS SUMBANGAN PEMBINAAN PENDIDIKAN (SPP) SEBAGAI ALAT PENGENDALIAN INTERNAL PADA SD NEGERI WEGOKNATAR - Elisabeth Susanti; Maria Nona Dince; Fransiscus De Romario (Jurnal Projemen UNIPA, 2025)
This study was conducted at SD Negeri Wegoknatar with the aim of analyzing the accounting information system for cash receipts of Education Development Contributions (Sumbangan Pembinaan Pendidikan/SPP) as an internal control tool. The research employed a qualitative method with a description approach. Data were collected throught observations and interviews with informants regarding the recording system for cash receipts has been implemented but remains basic and manual, without utilizing modern information technology. Moreover, the system lacks a written Standard Operating Procedure (SOP), increasing the potential risk of fraud. Internal control was also found to be ineffective due to weaknesses in risk assesment, control activities, and external information reporting. Consequently, the transparency and accountability of SPP fund management at SD Negeri Wegoknatar remain limited